Analysis of Vocabulary Definitions of the Word “Uspech” (“Success”): Problem of Verification of Linguoculturological Constructions - M. A. Eremina (Научный диалог)
A method for solving the actual problem of verification of linguocultural constructions is proposed. Attention is paid to the establishment of the correctness and effectiveness of the application of one of the types of semantic analysis in modern linguistic studies devoted to the concept of “success” and its lexical representatives. The proposed meta-research approach is aimed at identifying and searching for the causes of significant discrepancies in the results of definitional analysis when the theoretical base, scientific apparatus and research strategy coincide. This approach allows the author to consider a number of controversial cases of the use of definitional analysis associated with its object, subject and metalanguage, and to solve some important methodological issues: what kind of linguistic sources are involved in collecting material; how the definitional analysis of a polysemantic word is carried out; in what aspect the interlingual comparison of the dictionary definitions of one word is carried out; what advantages and disadvantages of different formats for describing semantic components are identified as a result of definitional analysis, etc. Critical analysis of research techniques alternates with constructive sentences for the semantic analysis of the dictionary definitions of the word success in modern Russian. General observations on the features of the application of the analytical method under consideration are proposed as conclusions.